The great divergence : hegemony, uneven development, and global inequality - S, Jomo K.; Jomo K. S. (Jomo Kwame Sundaram) (New Delhi : Oxford University Press, 2006)
Refers to the period since the late 19th century associated with what is seen as the age of imperialism. This volume consists of regional surveys of the transformation of the major regions of the South during the course of the long twentieth century. The regions covered include Latin America, Africa, the Middle East, India, and Southeast Asia.
Introduction / Jomo K.S. -- The concept of mode of production and theory of imperialism / Prabhat Patnaik -- Latin America and the world economy in the long twentieth century / José Antonio Ocampo -- Africa in the long twentieth century / Bill Freund -- Imperialism in Africa / Lance van Sittert -- The Middle East in the long twentieth century / Faruk Tabak -- Southeast Asia: imperial possession and dispossession in the long twentieth century / Maria Serena I. Diokno -- India in the long twentieth century / Sumit Sarkar -- Lenin's theory of imperialism today / Prabhat Patnaik.
Includes bibliographical references and index.
Keywords: Imperialism -- History -- 20th century; Developing countries -- Colonial influence; Developing countries -- Economic conditions